Efficacy and safety of anticoagulants on venous thromboembolism: a systematic review and network meta-analysis of randomized controlled trials - Weijie Fu; Maolin Zhao; Sheng Ding; Mei Xin; Ke Yang; Li Jiang; Fan Wu; Xiaochen Wu; Jian Wang; Jie Chen; Feng Gao; Siyi He (Frontiers in Pharmacology)
BackgroundAnticoagulants are the primary means for the treatment and prevention of venous thromboembolism (VTE), but their clinical standardized application still remains controversial. The present study intends to comprehensively compare the efficacy and safety of various anticoagulants in VTE.MethodsMedline, Embase, and Cochrane Library from their inception up to August 2023 were searched to compare the efficacy and safety of various anticoagulants in VTE. We extracted data on study settings, baseline characteristics, interventions, and outcomes, applying the intention-to-treat principle. Two researchers assessed study bias using the Cochrane tool, resolving disagreements through discussion or third-party adjudication. Network meta-analyses were performed based on Bayesian generalized linear models, and a frequentist framework with multivariate random effects was used to fit the model.ResultsIn terms of treatment, 58 trials with 119,417 patients proved eligible, while 125 trials with 225,414 patients were included in terms of prevention. All anticoagulants were found to reduce the recurrence or incidence of VTE compared with Placebo, of which high-level evidence indicated that direct thrombin inhibitors (TIs) and novel oral anticoagulants (NOACs) were the two most effective drugs. For treatment, low molecular weight heparin (LMWH), unfractionated heparin (UFH), and vitamin K antagonists (VKAs) significantly increased the risk of major bleeding in comparison to Placebo. For prevention, only UFH (OR 2.0, 95% CI 1.2–3.3) and NOACs (OR 1.8, 95% CI 1.2–2.6) showed significant increased risks in major bleeding. Additionally, after an exhaustive analysis of NOACs, analysis showed that apixaban (RR 0.5, 95%CI 0.17–1.46) had a superior performance in major bleeding compared to rivaroxaban (RR 3.87, 95%CI 1.48–10.09).ConclusionTIs and NOACs were superior in efficacy with minimal side effects, making them pivotal choices for both prevention and treatment of VTE. Clinical practitioners must carefully weigh drug characteristics, indications, and contraindications to optimize treatment outcomes.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=466775.